Biomechanics of swimming with interrelationships to fitness and performance - Cureton, T. K. (First International Symposium on "Biomechanics and Swimming, Waterpolo and Diving", 14-16 September 1970. Proceedings, 1971)
The generalized law for the human body moving through still water may be approximated by the following formula F- R =M V, where F =Propelling Force from Arms and Legs R = Resistance of the Water to the Body Moving Through it M = t4ass of the Body ~loved, W/g a = Average Acceleration. It is also true that when F = 0, then R equals 0. When the motion is considered as smooth motion, then the equation becomes, F- R =M v, where V is average velocity in forward motion. The equations have been validated by dragging a canoe through the water (8), measuring W/g for the canoe, the velocity changes with Karpovich's natograph, and also measuring the resistance at various velocities with Karpovich's resistograph, then computing force F. The F was then measured by the resistograph converted to a dynamograph to obtain a reasonably close check, by formula F- R =M v. Force and velocity vary, of course with different strokes, different sized and shaped bodies, the extent to which the body floats, and the position it takes while being propelled through the water. This means that no absolutely exact formula is possible for the complicated movements of the crawl, back crawl, breast or Dolphin strokes --but there are methods which throw considerable 1 ight on the mechanics of these strokes, which will be developed in this paper, but not an exact treatment of bow friction, eddy currents, stern wake drag and skin frictions. The body will be treated as a whole, then separately the legs and the arms, and the body only gliding without use of arms or legs. Since 1930 a certain amount of evidence has been accumulated which will be reviewed in this paper. The various studies by various authors wi11 be briefly summarized in this paper.